Determination of biometric measures to evaluate patient suitability for transoral robotic surgery. Issue 9 (29th October 2014) - Arora, Asit; Kotecha, Jalpa; Acharya, Amish; Garas, George; Darzi, Ara; Davies, D. Ceri; Tolley, Neil
Abstract Background Transoral robotic surgery (TORS) represents a novel treatment for oropharyngeal cancer and obstructive sleep apnea. Appropriate patient selection is crucial. The purpose of this study was to investigate whether anatomic biometric measures are useful to determine the feasibility of performing TORS. Methods Three surgeons independently evaluated feasibility in 51 soft‐fix cadavers. Transoral visualization was performed with 2 retractors commonly used in TORS. Seven anthropometric parameters and the degree of mouth opening were recorded. Results Mandibular body height, hyoid‐mental length, and neck circumference demonstrated significant differences between "suboptimal" and "adequate" visualization of base of tongue and epiglottis (p < .05). Limited mouth opening was associated with suboptimal visualization. Neck circumference had the strongest influence on predicting TORS feasibility. Conclusion Mandibular body height, hyoid‐mental length, and neck circumference in conjunction with the degree of mouth opening may determine patient suitability for TORS. Clinical evaluation is essential to validate their collective usefulness. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1254–1260, 2015